Anti-tumor and immunomodulation activity of polysaccharides from Dendrobium officinale in S180 tumor-bearing mice. (July 2022) - Sun, Chuanbo; Zhang, Nuo; Xu, Guangpei; Jiang, Ping; Huang, Shiping; Zhao, Qun; He, Yanfei
Graphical abstract: Highlights: DOP consisted of D-mannose, D-glucose, and D-galactose in a mole ratio of 3:2:1. DOP possesses antitumor and immunomodulation activity. DOP enhanced NK cell and CTL activity and increased the non-specific and tumor antigen-specific antibody titers. DOP could inhibit the growth of S180 tumors by improving the tumor immune microenvironment. Abstract: This study aims to explore the structural features and anti-tumor and immunomodulation activity of polysaccharides from Dendrobium officinale that were prepared using DEAE Sephadex A-50 and Sephadex G100. DOP structure was characterized using colorimetry, HPGPC, GC–MS, FT-IR, and NMR. The molecular weight of DOP was 1.89 × 10 5 Da. And the DOP consisted of D-mannose, D-glucose, and D-galactose in a mole ratio of 3:2:1. DOP could inhibit the growth of S180 tumors by promoting splenocytes proliferation, enhancing NK cell and CTL activity, and increasing the non-specific and tumor antigen-specific antibody levels. These findings suggested that DOP might be a potential antitumor agent with immunomodulatory activity.